Estimating Stature among Medical Students in Lalitpur, Tertiary Care Hospital, using Index and Ring Finger Length (Nepal Journal of Health Sciences, 2022)
Introduction: Anthropometry refers to a group of systematic methods for quantitatively measuring the dimensions of the human body and skeleton. It is the fundamental tool for biological anthropology that is closely related to determining an individual’s height based on the available information.Objective: Medical and dental students in Nepal will use finger lengths to derive a regression equation to calculate an individual’s height in a tertiary care hospital.Methods: A cross-sectional study included 250 healthy Nepali students from KISTMCTH (145 females and 105 men). Using SPSS software version 17, the index (2DL) and ring (4DL) finger lengths were measured in order to create a regression formula.Results: Males outperform females in terms of Pearson’s correlation, coefficient of determination, and regression equation. Linear regression analysis was used to estimate stature using the assessed factors that were statistically significant (p 0.05) for both genders.Conclusions: Forensic professionals and anthropologists will find it useful to be able to estimate stature from the length of the finger when identifying a person from skeletal remains.